A Large Left Ventricle Myxoma: Presenting with Epigastric Pain and Weight Loss - Solmaz Fakhari; Eissa Bilehjani (Case Reports in Cardiology)
Cardiac myxomas are the most common benign tumors found in the heart. They usually appear in the left atrium. Those originating from the left ventricle (LV) are rare. Although clinical presentation may vary, dyspnea and embolism are the most commonly reported symptoms. In the present case study, a 27-year-old woman with a large myxoma originating from the left ventricular free wall is studied. She had atypical complaints, mainly epigastric discomfort, nausea, vomiting, and anorexia. She was hospitalized for acute abdomen, but subsequent investigations revealed a large myxoma that fully filled the LV and severely compromised the flow of the aortic and mitral valves. After successful emergency tumor resection, all symptoms disappeared. The uncommon presentation caused by these tumors is discussed in this study.